CHARACTERIZATION OF HIGH-PRESSURE TURBINE (HPT) FIRST-STAGE TURBINE BLADE IN AIRPLANE JET ENGINES - Aufa Ramadani, Lutfi
Airplanes are one of the most frequently used mode of transportation and have jet engines to power them in the air. Jet engines often experience failures that occur in turbine blades. The critical pressure and temperature conditions subjected to high-pressure turbine (HPT) could potentially cause failure. This study aims to identify the coating, cooling system, and materials used in the HPT first-stage turbine blades of the CFM56-7B and CFM56-5C engines. The methods used are visual observation, metallography using a light optical microscope, and Energy Dispersive Spectroscopy (EDS) characterization. The results of this characterization are that the coating used on the HPT first-stage CFM56-7B turbine blade has a thermal barrier coating made of yttria-stabilized zirconia and Pt-aluminide bond coat, has a cooling system with film impingement cooling, and uses single crystal superalloy material with a chemical composition similar to Rene N5. Meanwhile, the HPT first-stage CFM56-5C turbine blade has a Pt-aluminide coating, has a cooling system with film impingement cooling, and uses a polycrystalline superalloy material with a chemical composition similar to Rene 80.